Incidence of Venous Thromboembolism in Hospitalized Coronavirus Disease 2019 Patients: A Systematic Review and Meta-Analysis - Zhang, Chi; Shen, Long; Le, Ke-Jia; Pan, Mang-Mang; Kong, Ling-Cong; Gu, Zhi-Chun; Xu, Hang; Zhang, Zhen; Ge, Wei-Hong; Lin, Hou-Wen (Frontiers in Cardiovascular Medicine, 2020)
Background: Emerging evidence showed that coronavirus disease 2019 (COVID-19) was commonly complicated with coagulopathy, and venous thromboembolism (VTE) was considered as a potential cause of unexplained death. Whereas, information on the incidence of VTE in COVID-19 patients remains unclear. Methods: English-language databases (PubMed, Embase, Cochrane), Chinese-language databases (CNKI, VIP, WANFANG), and preprint platform were searched to identify studies that concerned the data of VTE occurrence in hospitalized COVID-19 patients. Pooled incidence and relative risks (RRs) of VTE were estimated by random-effects model. Variations were examined based on clinical manifestations of VTE (pulmonary embolism-PE and deep vein thrombosis-DVT), disease severity (severe patients and non- severe patients), and rate of pharmacologic thromboprophylaxis (≥ 60% and <60%). Sensitivity analyses were conducted to strengthen the robustness of results. Meta-regression was performed to explore the risk factors associated with VTE in COVID-19 patients. Results: A total of 17 studies involving 1,913 hospitalized COVID-19 patients were included. The pooled incidence of VTE was 25% (95% CI, 19%-31%; I2, 95.7%), with significant difference between the incidence of PE (19%; 95% CI, 13%-25%; I2, 93.2%) and DVT (7%; 95% CI, 4%-10%; I2, 88.3%; Pinteraction <0.001). Higher incidence was observed in severe COVID-19 patients (35%; 95 CI%, 25%-44%; I2, 92.4%) than that in non-severe patients (6%; 95 CI%, 3%-10%; I2, 62.2%; Pinteraction <0.001). The high rate of pharmacologic thromboprophylaxis in COVID-19 patients (≥ 60%) was associated with a lower incidence of VTE compared with low pharmacologic thromboprophylaxis rate (<60%) (19% vs. 40%; Pinteraction =0.052). Severe patients had a 3.76-fold increased risk of VTE compared with non-severe patients (RR, 4.76; 95% CI, 2.66-8.50; I2, 47.0%). Sensitivity analyses confirmed the robustness of primacy results. Conclusions: This meta-analysis revealed the estimated VTE incidence was 25% in hospitalized COVID-19 patients. Higher incidence of VTE was observed in COVID-19 patients with severe condition or with low rate of pharmacologic thromboprophylaxis. Assessment of VTE risk is strongly recommended in COVID-19 patients, and effective measures of thromboprophylaxis should be timely taken for patients with high risk of VTE.